Industrial experience with Fukushima Daiichi Accident wastewater treatment: Part I. Issue 8 (August 2021) - Pabby, A.K.; Swain, B.; Mittal, V.K.; Valsala, T.P.; Sathe, D.B.; Bhatt, R.B.
Abstract : Based on existing information, this article focuses on the challenges of radionuclide removal and analysis of the performance of processes associated with the treatment of a large-scale volume of wastewater at the site of the Fukushima Daiichi nuclear disaster, which occurred ten years ago. The first instalment, which appears here, provides an introduction to the work and processes used. It discusses reverse osmosis and the role it has played in treating contaminated sea-water at the site. It also describes a laboratory-scale study and the first of two schemes – involving what is referred to as the Simplified Active Water Retrieve and Recovery (SARRY) system – that are used to purify reverse osmosis retentate.